Comparative efficacy different resistance training protocols on bone mineral density in postmenopausal women: A systematic review and network meta-analysis - Wang, Zhenyu; Zan, Xingchun; Li, Yongjie; Lu, Yue; Xia, Yuan; Pan, Xinyong (Frontiers in Physiology, 2023)
Objective: To systematically review the effects of different resistance training (RT) protocols on bone mineral density (BMD)in postmenopausal women. Methods: Randomized controlled trials (RCTs) on the RT in improvingBMDfor postmenopausal women were searched in databases including ProQuest, PubMed, Cochrane Library, Embase, and Web of Science.The retrieval time range wasfrom the establishment of the database to May 2022.The included literature was independently screened and relevant datawas extracted by two reviewers. The systematic review followed the Joanna Briggs Institute (JBI)methodology for reviews of quantitative evidence.Quality of Risk was assessed using the Physical Therapy Evidence Database (PEDro) scale, risk of bias was assessedusing the Cochrane RoB2 tooland a network Meta-analysis was performed on the data using Stata 16.0. Results:A total of 19 studies, which included 919 subjects, were eventually acquired. The results of the network Meta-analysis showed that moderate intensity RT was superior in improving lumbar spine BMD (LS BMD) and femoral neck BMD (FN BMD) compared to the control group (as per usual daily life), with a statistically significant difference (P<0.05). There was, however, no statistically significant difference between the groups in terms of increasing total hip BMD (TH BMD) and trochanter BMD (Troch BMD), although moderate intensity trainingtends to increase BMD(P>0.05). In addition, when training frequency is taken into consideration, 3 days/week of moderate intensity training (3MI) was superior to2days/week (2MI) in improvingLS BMD, and moderateintensity trainingwas superior to low and highintensity resistance trainings at training frequency of 3days/week, withstatistically significant differences (P<0.05). The cumulative probability ranking results indicated that 3MI was the optimal option in improving LS, FN, TH and Troch BMD. Subgroup analyses combining interventions time showedthat for LS and FN BMD, 3MI protocolwith intervention duration within one year (≤48weeks) had significant advantage over other interventions, while this advantage was no longer significant with the intervention duration of more than one year(＞48weeks). Conclusions:Current evidence shows that moderate intensity resistance training for 3days/week can be preferred clinically to improve BMD in postmenopausal women, and it is recommended that the duration of the same training should not exceed one year. Nevertheless, more high-quality studies are needed to verify the above conclusions.